2016
DOI: 10.1155/2016/9810270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Dexamethasone Implant in Patients with Diabetic Macular Edema at Tertiary Centers in Korea

Abstract: Purpose. To evaluate the real-world efficacy and safety of the dexamethasone implant (DEX implant) in patients with diabetic macular edema (DME). Methods. Retrospective, multicenter, and noncomparative study of DME patients who were treated with at least one DEX implant. A total of 186 eyes from 165 patients were included. Best-corrected visual acuity (BCVA), central retinal thickness (CRT), complications, and number of retreatments were collected. Data at baseline and monthly for 6 months were analyzed. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
8
19
0
Order By: Relevance
“…Another real-world study conducted in Korea found that in patients with DME, DEX improved mean BCVA from 0.60 logMAR at baseline to 0.49 logMAR at 3 months and 0.55 log-MAR at 6 months (mean improvement of 6 and 3 approximate ETDRS letters, respectively), and the mean CRT improved from 491.6 µm at baseline to 357.7 µm at 3 months and 412.5 µm at 6 months. 14 Consistent with the present study, 48.9% of patients received additional treatment with intravitreal anti-VEGF therapy or a second DEX injection within 6 months, and the mean treatment-free interval was 4.4 months after the first DEX injection. Finally, in a real-world study of the dosing regimens of DEX used for DME treatment in France, the mean DEX injection interval was 4.9 months, with an average of 2.4 injections administered per year for patients with DME.…”
Section: Discussionsupporting
confidence: 89%
“…Another real-world study conducted in Korea found that in patients with DME, DEX improved mean BCVA from 0.60 logMAR at baseline to 0.49 logMAR at 3 months and 0.55 log-MAR at 6 months (mean improvement of 6 and 3 approximate ETDRS letters, respectively), and the mean CRT improved from 491.6 µm at baseline to 357.7 µm at 3 months and 412.5 µm at 6 months. 14 Consistent with the present study, 48.9% of patients received additional treatment with intravitreal anti-VEGF therapy or a second DEX injection within 6 months, and the mean treatment-free interval was 4.4 months after the first DEX injection. Finally, in a real-world study of the dosing regimens of DEX used for DME treatment in France, the mean DEX injection interval was 4.9 months, with an average of 2.4 injections administered per year for patients with DME.…”
Section: Discussionsupporting
confidence: 89%
“…41 Therefore, inhibiting inflammatory pathway mediators could be one of the therapeutic options for the ME and the use of intravitreal steroid therapy, including the dexamethasone implant, has been increasingly used for the treatment of ME in DR and RVO patients. [4][5][6][7]42,43 In a patient with ME, a certain mechanism (VEGF pathway or inflammatory pathway) might contribute more to the development of ME. This eventually affects the treatment response to a certain treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…3 Various treatments, such as intravitreal anti-VEGF injections and intravitreal dexamethasone injections have shown good visual and anatomic outcomes. [4][5][6][7][8][9][10][11][12][13] However, some ME cases show suboptimal response to these treatment modalities.…”
mentioning
confidence: 99%
“…Other real-life studies have also shown similar improvements in VA and CRT without serious adverse events, mainly in smaller series over shorter follow-up periods. [31][32][33][34][35][36] In our population of DME patients, IDI considerably improved the VA relative to baseline in both treatment-naive and previously treated patients, suggesting that IDI therapy offers bene ts to both types of patient. Nevertheless, naive eyes maintained a better mean VA than previously treated eyes at all time points studied.…”
Section: Discussionmentioning
confidence: 69%